Female Fertility Preserving Practices at a Pediatric Unit: A Challenge of Multiprofessional and Multidisciplinary Cooperation. Issue 2 (March 2016) - Terenziani, Monica; Meazza, Cristina; Massimino, Maura; Viganò, Paola; Gandola, Lorenza; Mangili, Giorgia; Raspagliesi, Francesco; Biasoni, Davide; Podda, Marta; Veneroni, Laura; Filippi, Francesca; Riccipetitoni, Giovanna; et al.
Introduction: Being able to have children could have an important positive effect on the future lives of pediatric cancer survivors. Working at a cancer institute makes us responsible for filling the gaps in our knowledge in this area of patient care. Methods: We describe our activities in a series of young females diagnosed with cancer and evaluated for fertility preservation options. We discuss the developed skills and organization as well as the practical difficulties encountered in managing fertility preservation. Results: Since September 2012, laparoscopy and cryopreservation of cortical ovarian tissue has been performed in 16 girls (with ovary transposition in 3, and after several cycles of chemotherapy in 5) and egg banking in 4 young women (before chemotherapy in 2 and several years after treatment in 2). Conclusions: Recommendations on fertility preservation indicate that discussing the problems early on is crucial to future success. It is unthinkable to simply provide information and offer the opportunity to choose a fertility preserving technique without helping and accompanying patients and their families in their decisions and choices on the matter.